Penerapan Pembelajaran Menyenangkan menggunakan Media Bantu Sederhana terhadap Anak-Anak di Kawasan Kopi-Kopi Honelama - Rumpaisum, Christine M.; Sinambela, Mindo H.; Borean, Sutarman; Napitupulu, Citra R.; Wanimbo, Kojo (Neolectura, 2024)
Community Service activities of STKIP Abdi Wacana are carried out as a form of concern for educational conditions and at the same time as the implementation of the Tridharma of Higher Education. The characteristics of children at the age of pre-school, elementary school to junior high school in the Papua Mountains tend to be more interested in concrete things so that they need a more tangible learning tool. Learning habits experienced at school by taking notes make children uninterested in learning so that after school, they will spend their free time just playing without learning at all. Creating a fun learning atmosphere by utilising a simple learning aid and the concept of jarimatika is one option in attracting children's interest and motivation to learn. This is what underlies the Community Service activities by lecturers and students of STKIP Abdi Wacana Wamena. The implementation of Community Service activities is located in the Honelama Coffee area. Based on the results of brief oral interviews with the children who participated in the activities, it turned out that they were very happy with the new learning experience and different from what they experienced at school. In addition, the response of the children's parents was very positive where they hoped that children in the Honelama Coffee-Coffee Area could be given guidance on a regular basis.